2013
DOI: 10.1155/2013/208412
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-1 Infection and Innate Sensing in Different Types of Primary Human Monocyte-Derived Macrophages

Abstract: Macrophages play an important role in human immunodeficiency virus (HIV) pathogenesis and contribute to establishment of a viral reservoir responsible for continuous virus production and virus transmission to T cells. In this study, we investigated the differences between various monocyte-derived macrophages (MDMs) generated through different differentiation protocols and evaluated different cellular, immunological, and virological properties. We found that elevated and persistent HIV-1 pWT/BaL replication cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The apparent discrepancy between these results and ours can be, at least in part, explained by the different protocol used for monocyte culture, which may greatly influence the ability of MDM to activate innate immune reactions and support HIV-1 replication. To this regard, it has been recently shown that MDM generated in the presence of M-CSF are more permissive to HIV-1 replication, but paradoxically have a strongest innate immune response [ 78 ]. Furthermore, additional studies pointed to an up-regulated expression of A3A as the causal factor of the restriction of HIV-1 replication elicited by different conditions in myeloid cells [ 53 , 79 - 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The apparent discrepancy between these results and ours can be, at least in part, explained by the different protocol used for monocyte culture, which may greatly influence the ability of MDM to activate innate immune reactions and support HIV-1 replication. To this regard, it has been recently shown that MDM generated in the presence of M-CSF are more permissive to HIV-1 replication, but paradoxically have a strongest innate immune response [ 78 ]. Furthermore, additional studies pointed to an up-regulated expression of A3A as the causal factor of the restriction of HIV-1 replication elicited by different conditions in myeloid cells [ 53 , 79 - 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of wild-type MDMs to sense exogenous HIV-1 or the replicating virus has not been fully clarified. Some studies argue that HIV-1 does not lead to detectable activation of NFkB or production of IFN-ß in MDMs [47,48 ], while other studies suggest that MDMs respond to HIV-1 by expressing IFN-stimulated genes [49] and activating the inflammasome [50] (although the requirement for viral components was not confirmed in the latter study).…”
Section: Monocyte-derived Macrophagesmentioning
confidence: 69%
“…Means Ϯ SD from at least three independent donors performed in duplicate are shown. *, P Ͻ 0.05; **, P Ͻ 0.005; ***, P Ͻ 0.0005. ferentiation in cell culture (e.g., macrophage colony-stimulating factor [M-CSF] instead of granulocyte-macrophage colony-stimulating factor [GM-CSF]), which affects macrophage susceptibility to HIV-1 infection (29) and also dNTP intracellular levels, both parameters being higher in M-CSF-differentiated macrophages (see Fig. S2 in the supplemental material) (data not shown).…”
Section: Discussionmentioning
confidence: 99%